2017
DOI: 10.1002/2016ja023285
|View full text |Cite
|
Sign up to set email alerts
|

Fast‐moving diffuse auroral patches: A new aspect of daytime Pc3 auroral pulsations

Abstract: Auroral pulsations are a convenient diagnostic of wave‐particle interactions in the magnetosphere. A case study of a daytime Pc3 (22–100 mHz) auroral pulsation event, measured with a ~2 Hz sampling all‐sky camera at South Pole Station (74.4°S magnetic latitude) on 17 May 2012, is presented. The daytime Pc3 auroral pulsations were most active in a closed field line region where the aurora was dominated by diffuse green‐line emissions and within ±2 h of magnetic local noon. Usually, but not always, the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 37 publications
8
6
0
Order By: Relevance
“…Unfortunately, the calibrated monochromatic all‐sky imager at SPA did not operate in the 2016 season, which made it impossible to quantitatively estimate the absolute values of the auroral luminosity for Event 1. However, our earlier study has revealed that the green line emission of daytime diffuse auroral pulsations has several hundred Rayleighs (see Figure b of Motoba et al, ), which is in good agreement with the small‐amplitude chorus wave modulation observed in space, suggesting it is responsible for the daytime auroral pulsations. On the other hand, no chorus data were available at TH‐E for Event 2, which leaves room for considering another possibility, for example, compressional Pc3 magnetic pulsations may act as a direct driver for scattering keV electrons (Brito et al, , ; Rae et al, ).…”
Section: Summary and Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Unfortunately, the calibrated monochromatic all‐sky imager at SPA did not operate in the 2016 season, which made it impossible to quantitatively estimate the absolute values of the auroral luminosity for Event 1. However, our earlier study has revealed that the green line emission of daytime diffuse auroral pulsations has several hundred Rayleighs (see Figure b of Motoba et al, ), which is in good agreement with the small‐amplitude chorus wave modulation observed in space, suggesting it is responsible for the daytime auroral pulsations. On the other hand, no chorus data were available at TH‐E for Event 2, which leaves room for considering another possibility, for example, compressional Pc3 magnetic pulsations may act as a direct driver for scattering keV electrons (Brito et al, , ; Rae et al, ).…”
Section: Summary and Discussionsupporting
confidence: 86%
“…This means that the daytime auroral pulsations measured at a given point (i.e., the zenith of SPA) were produced by the fast spatial motion of nonpulsating auroral patches not by the temporal luminosity variation in a pulsating auroral patch. Such 2‐D morphological signatures of the daytime auroral pulsations are very similar to those reported by Motoba et al (), as was mentioned in the introduction.…”
Section: Observationssupporting
confidence: 89%
See 2 more Smart Citations
“…The 630-nm emission data are used not only for auroral study, but also airglow observation such as polar patches in the polar cap region. Panchromatic and color all-sky camera observations have been also continuously conducted for dayside auroral pulsation study [e.g., Motoba et al, 2017] even during new moon periods, as well as narrow/wide FOV camera observations mentioned in the previous section. At the South Pole and McMurdo stations, all the cameras can be operated for 24 hours a day between April and August.…”
Section: Locations and Acquired Data Of The Wmi Imagersmentioning
confidence: 99%